Jeg tror for at elske - Horneman-Thielcke, Thomas Emil (Dansk Teologisk Tidsskrift, 2009)
The purpose of this article, “I believe in order to love: Negative theology in the writings of St. John of the Cross”, is threefold. First we see how St. John uses classical negative theology as the basis of his spiritual programme. This is of especial interest because John manages to transform the theoretical method of apophatic discourse into a practical spiritual process. In this spiritual programme, discourse about God results in the soul’s refusal of the entire creation in an attempt to move closer to God through faith. This is particularly obvious in his metaphorical expression “the dark night”, which can be best interpreted in the light of Christ's passion, death and resurrection. The second purpose of this article is exactly to show how St. John uses the agony and pain of Christ as a model for the soul’s suffering in “the dark night”. Thirdly the aim is to put St. John’s negative theology in a contemporary and postmodern theological discourse and, in the light of this study, see if a new theological reading and understanding of it is possible.